AKTIVITAS TANAH LAPUKAN BREKSI VULKANIK DAN IMPLIKASINYA TERHADAP KEKUATAN FONDASI DI JATINANGOR - -, Irvan Sophian; -, Zufialdi Zakaria; -, Yuyun Yuniardi (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Jatinangor require public facility. The facility need strength of soil bearing capacity for stable foundation in occupying each soil mass. Soil type in this area is CH ( clay of high plasticity) and MH (silt of high plasticity). Based on diagram of Cassagrande, area research reside between U-line and A-line, and soil type generally is CH, clay high plasticity.At soil which have medium-high activity, allowable soil bearing capacitry ( qa) for continuous foundation is between 31.450 until 52.884 T/m2. Soil bearing capacity ( qa) with activity number (A) show negative relationship ( R - 0.804058). Increasing soil activity caused decreasing soil baring capacity.Instruction of Environmental Monitoring Plas is done especially monitoring at condition of house building and also other medium building like drainage channel and bridge etcetera. Environmental monitoring is required as effort to anticipate damages of arising out effect of negative impact. Small damage is properly attention or improve repaired before becoming is big.